Nurses Knowledge regarding Permanent Pacemaker Care for Adult Patients with Cardiac Rhythm Disorder : Nurses Knowledge regarding Permanent Pacemaker Care - Aimen, Umm E; Mansoor, Summaiya; Rafique, Nasim; Ali, Amjad; Nazir, Iqra; Fatima, Rija; Waris, Shagufta; Kosar, Lubna (Pakistan Journal of Health Sciences, 2023)
Now a day, number of implantations increases day by day. It’s crucial to evaluate the understanding of patients and their caretakers to prevent any issues or malfunctions and offer quick treatment. Objective: To assess nurses’ knowledge regarding permanent pacemaker care for adult patients with cardiac rhythm disorder. Methods: Descriptive Cross-sectional study conducted in Punjab institute of cardiology. A total of 185 the nurses working on the clinical side were selected based on inclusion and exclusion criteria. The questionnaire was used to collect data analyzed using SPSS with statistical test chi-square with p < 0.05 for categorical variable. Results: According to this study, most of the participants (77.3%) were women aged 21 to 30 years, unmarried (57.3%), and had completed their diploma (50.8%). The study found that 66.5% of nurses were with satisfactory level of knowledge in nursing care for adult patients with pacemakers, while 33.5% had an unsatisfactory level of knowledge. The knowledge of nurses who held a BSN or a POST RN qualification was significantly higher than those who only held a diploma with a p-value of 0.001. Conclusions: Majority of the participants possessed satisfactory knowledge regarding the care of patients with permanent pacemakers. The study also revealed a significant association between the level of education of nurses and their knowledge scores. The study concludes that consistency in the provision of education is necessary for the enhancement of nurses’ knowledge, expertise, and competencies in providing care to patients with permanent pacemakers